New insights into the environmental performance of perovskite-on-silicon tandem solar cells – a life cycle assessment of industrially manufactured modules. Issue 12 (23rd May 2022) - Roffeis, Martin; Kirner, Simon; Goldschmidt, Jan-Christoph; Stannowski, Bernd; Perez, Laura Miranda; Case, Christopher; Finkbeiner, Matthias
Abstract : A life cycle assessment points to environmental advantages of industrially manufactured perovskite-on-silicon tandem cell (PST) modules over silicon hetero-junction cell (SHJ) modules. Abstract : LCA studies of perovskite-on-silicon tandem (PST) cells have so far been heavily reliant on laboratory data and process data from test facilities to project environmental impacts, producing results that differ significantly from one another. This paper reports on potential environmental impacts of an industrially manufactured PST module. Based on process data from a volume manufacturing line in Brandenburg, Germany, a comprehensive life cycle assessment (LCA) was performed using the ReCiPe 2016 v1.1 method. The production of one module was estimated with a global warming potential (GWP) of 434 kg CO2 eq., terrestrial ecotoxicity potential of 598 kg 1, 4-DB eq., freshwater consumption (FWC) of 14 m 3, and fossil and metal depletion potential (FDP and MDP) of 164 kg oil eq. and 2034 g Cu eq., respectively. In line with other studies, the environmental performance of the PST module was largely influenced by the amount of energy consumed in the course of production, making the silicon wafer production the determining process step in most impact categories considered. Exceptions were found with the metal depletion potential (MDP) and terrestrial ecotoxicity potential (TETP), where copper, aluminum and float glass implemented in the cell manufacturing and module production process decisively determined the impacts of production. The built-in lead, on the other hand, had no significant influence on the result of the toxicity-specific impact categories in ReCiPe, even if complete lead emission was assumed. The results were also analysed and compared to those of a silicon hetero-junction solar cell (SHJ) module, modelled analogously to the PST production process. While we found the overall environmental impact of the PST module per piece to be higher than that of the SHJ module in most impact categories (up to 7%) due to the additional process steps, a comparison made on the basis of kW h produced shows advantages for the PST module with 6–18% across all impact categories, as a higher efficiency overcompensates the higher environmental burden of production, assuming the same lifetime for both modules.